A rational decision-making learning model to enhance elementary students' environmental understanding - Galih Dani Septiyan Rahayu; Asep Kurnia Jayadinata; Jajang Bayu Kelana (Indonesian Journal of Educational Development (IJED), 2026)
Environmental literacy is a critical competency for elementary students, yet many pedagogical approaches lack structured frameworks connecting environmental issues to real-world decision-making. This study aimed to enhance students' environmental understanding through a rational decision-making learning model supported by interactive digital multimodal teaching materials based on socioscientific issues (SSI). A pre-experimental one-group pretest–posttest design was employed with 75 fifth-grade students in Cimahi City, West Java, selected through purposive sampling. Data were collected using a validated environmental understanding test that measured knowledge of causes, impacts, and solutions to environmental problems, and were then analyzed using Wilcoxon tests. Results showed a statistically significant improvement in students' environmental understanding. The model enabled students to think systematically by connecting causes, consequences, and solutions to environmental problems, while promoting critical reasoning and active engagement in learning. These findings suggest that integrating decision-making frameworks with multimodal SSI materials can effectively support environmental literacy in primary education. Future studies should apply this model across broader populations and examine its long-term impact on students' environmental attitudes and behavior. This study is limited to fifth-grade students in a single city; thus, its generalizability requires further investigation.